1977
DOI: 10.1007/bf02894418
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction of aflatoxins from contaminated agricultural products

Abstract: and Summary Solvent extraction of agricultural products has been suggested as an effective means of removing aflatoxins from mold‐damaged commodities. The use of various polar solvents such as the azeotrope of acetone‐hexane‐water and of 2‐propanol‐water, aqueous acetone, and aqueous ethanol has been reported in the literature. This paper examines the overall aspects of solvent extraction, in particular the use of the azeotrope of 2‐propanol‐water, to remove aflatoxins from prepress solvent extracted cottonsee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…The second part of the study involved estimation of aflatoxin content in methanol/water extracts of unspiked and AFB1-spiked animal feeds, whole grain feed corn, and yellow ground corn meal samples using RT-iqPCR. Methanol/water was chosen because it is the commonly used solvent for animal feeds and feed grains for extraction of aflatoxins and the use of water and hydroxylated solvents like methanol is highly recommended to facilitate the effective release of aflatoxins into the extractant solution [ 26 , 27 ]. The analysis of feedstuffs often involves several steps of extraction, filtration, sample cleanup, and concentration before subjecting to mycotoxin assays.…”
Section: Resultsmentioning
confidence: 99%
“…The second part of the study involved estimation of aflatoxin content in methanol/water extracts of unspiked and AFB1-spiked animal feeds, whole grain feed corn, and yellow ground corn meal samples using RT-iqPCR. Methanol/water was chosen because it is the commonly used solvent for animal feeds and feed grains for extraction of aflatoxins and the use of water and hydroxylated solvents like methanol is highly recommended to facilitate the effective release of aflatoxins into the extractant solution [ 26 , 27 ]. The analysis of feedstuffs often involves several steps of extraction, filtration, sample cleanup, and concentration before subjecting to mycotoxin assays.…”
Section: Resultsmentioning
confidence: 99%
“…For example it has been reported that extraction with 80% isopropanol completely removed aflatoxins in cottonseed and peanut meal, but it also removed between 8.7% and 9.5% in meal solids. 186 Adsorption Some adsorbents can bind and remove mycotoxins from aqueous solutions. 20,171,187 Two extensively suggested mycotoxin binding agents are active charcoal and bentonite.…”
Section: Extraction With Solventsmentioning
confidence: 99%
“…The energy of dissolution required with these non-triglyceride components are apparently higher than with the triglycerides, and the nontriglyceride components remain in the defatted meal after solvent extraction. Hence, gossypol and aflatoxins are reactively detoxified or physically removed by multiple extractions with polar solvents (1,2).…”
mentioning
confidence: 99%